2011
DOI: 10.1108/00021461111177594
|View full text |Cite
|
Sign up to set email alerts
|

A triple hurdle model of US commercial bank use of guaranteed operating loans and interest assistance

Abstract: Purpose -The purpose of this paper is to estimate a three-equation model of US commercial bank usage of the Farm Service Agency's (FSA) guaranteed operating loan and interest assistance programs. Also, to identify the key farm and banking variables that affect the decision to use loan guarantees and the volume of loans with interest assistance. Design/methodology/approach -A triple hurdle, three-equation system is estimated to model three decisions: to participate in the FSA operating loan program; whether to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Ahrendsen et al (2004) found the use of guaranteed interest assistance was associated with greater financial stress. Utilizing a bank portfolio model, Ahrendsen et al (2011) found that state-level indicators of increased farm financial risk and bank lending risk lead to increased usage of FSA-guaranteed loan programs.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 99%
“…Ahrendsen et al (2004) found the use of guaranteed interest assistance was associated with greater financial stress. Utilizing a bank portfolio model, Ahrendsen et al (2011) found that state-level indicators of increased farm financial risk and bank lending risk lead to increased usage of FSA-guaranteed loan programs.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 99%
“…During periods of significant financial stress that affect the entire economy, the vulnerability of farm businesses in coping with increased business risks can become a concern (Dixon et al, 2011;Escalante et al, 2004;Phillips and Katchova, 2004). Some studies clarify the relative strength of certain farm enterprises and regional farm industries in withstanding economic and natural shocks that threaten business efficiency and viability (Ahrendsen et al, 2011;Dixon et al, 1999;Koenig and Sullivan, 1993). Although repayment records of farm borrowers have been notably better than non-farm clients of commercial banks during the recession of the late 2000s (Li et al, 2013), special attention during such difficult times would still be naturally drawn toward validating the endurance of FSA borrowers, given their relatively "marginal" status compared to other farmers.…”
mentioning
confidence: 99%
“…The borrower region was defined as the ten USDA Farm Production regions (US Department of Agriculture, Economic Research Service, 2010). Distinct regional differences in FSA loan programs, as shown in previous studies, would suggest regional differences in loan duration (Dodson and Koenig, 2003;Ahrendsen et al, 2011).…”
Section: Model Specificationmentioning
confidence: 58%
“…Previous studies on guaranteed loans have focused on examining factors influencing banks' decisions on participating in guaranteed loans programs (Settlage et al, 2006;Ahrendsen et al, 2011;Dodson, 2014), while others have focused on identifying factors affecting volume of loan guarantees, loss claims, and principal outstanding for both OL and FO loans (Dixon et al, 1999;Settlage et al, 2001a, b). The latter are more relevant to this analysis and merit further discussion.…”
Section: Related Studiesmentioning
confidence: 99%